2022
DOI: 10.1371/journal.ppat.1010407
|View full text |Cite
|
Sign up to set email alerts
|

GH18 family glycoside hydrolase Chitinase A of Salmonella enhances virulence by facilitating invasion and modulating host immune responses

Abstract: Salmonella is a facultative intracellular pathogen that has co-evolved with its host and has also developed various strategies to evade the host immune responses. Salmonella recruits an array of virulence factors to escape from host defense mechanisms. Previously chitinase A (chiA) was found to be upregulated in intracellular Salmonella. Although studies show that several structurally similar chitinases and chitin-binding proteins (CBP) of many human pathogens have a profound role in various aspects of pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 66 publications
2
20
0
Order By: Relevance
“…In line with these results of host cell-driven chiA inductions and potential targets on host cells, we found that the mutation of chiA leads to the diminished attachment of S. Typhimurium to human IEC and subsequently to less invasion (Fig 1A and 1B). Our results provide strongly increased evidence towards two very recent studies of S. Typhimurium and S. Typhi, which demonstrated that ChiA has an influence on virulence, promoting adhesion to human epithelial cells, followed by increased invasion [26,27]. However, those studies did not explore ChiA expression, regulation, and secretion phenotypes, dependent on polarized cells.…”
Section: Plos Pathogenssupporting
confidence: 68%
See 1 more Smart Citation
“…In line with these results of host cell-driven chiA inductions and potential targets on host cells, we found that the mutation of chiA leads to the diminished attachment of S. Typhimurium to human IEC and subsequently to less invasion (Fig 1A and 1B). Our results provide strongly increased evidence towards two very recent studies of S. Typhimurium and S. Typhi, which demonstrated that ChiA has an influence on virulence, promoting adhesion to human epithelial cells, followed by increased invasion [26,27]. However, those studies did not explore ChiA expression, regulation, and secretion phenotypes, dependent on polarized cells.…”
Section: Plos Pathogenssupporting
confidence: 68%
“…Chitinases are virulence factors in many pathogenic bacteria, important for the colonization of organs [18,19], attachment and invasion of host cells [20][21][22], promoting intracellular survival [23,24], and modulating the host immune response [25]. For S. Typhimurium and S. Typhi, a contribution of chitinases to the pathogenicity of both serovars has been shown very recently [26,27]. Chitinase-dependent remodeling and interaction with surface glycans promote the adhesion and invasion of intestinal epithelial cells (IEC) by Salmonella.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, chitinases, which hydrolyze chitin polymers into N-acetyl glucosamine oligomers, are a well-studied family of glycoside hydrolases in pathogens. Recent work has characterized Salmonella’s GH18 family chitinases and have shown them to be important for epithelial adhesion and invasion (Devlin et al ., 2021; Chandra et al ., 2022). Chitinases have been identified as important virulence factors for several other pathogenic bacterial species including Legionella pneumophila (Rehman et al ., 2020), Listeria monocytogenes (Chaudhuri et al ., 2013), Vibrio cholerae (Mondal et al ., 2014), and Adherent-invasive Escherichia coli (Low et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the bacteria develop a series of strategies to resist the damages by ROS. Some of the bacteria, such as Salmonella typhimurium [ 11 ], Listeria monocytogenes [ 12 ], and Pseudomonas aeruginosa [ 13 ], can interfere with the activity of ROS generation machinery in neutrophils. Unraveling the regulatory mechanism of ROS production in neutrophils in the context of pathogen-host interaction may lead to new strategies for the treatment of bacterial infection.…”
Section: Introductionmentioning
confidence: 99%